Occurrence of pathogens in watermelon and pumpkin crops in the State of Paraiba - Soares, Maria Gilmara de Oliveira (2016)
By constitute an important food source, watermelon and pumpkin plantations are commonly grown on Paraíba backlands, but little is known about the occurrence of disease-causing pathogens, which limit their productivity and income to producers. With objective to get information about the viral and fungal pathogens occurrence in pumpkin and watermelon crops in producing counties located in the backlands of Paraiba, samples with symptoms of mosaic and leaf distortion, typical of viral etiology of disease were collected and analyzed by "Enzyme linked immune sorbentassay" (Elisa) Indirect for species Papaya ring spot virus, type watermelon (PRSV-W), Watermelon mosaic virus (WMV), Zucchini yellow mosaic virus ( ZYMV) and Cucumber mosaic virus (CMV). The double diffusion test in Agar was used to verify the presence of Squash mosaic virus (SqMV). In contrast, samples collected with fungal disease symptoms were analyzed based on the isolation of the pathogen and viewing their morphological characteristics under an optical microscope. In pumpkin, there was prevalence of ZYMV and PRSV-W in single and mixed infections, and higher incidence of Cladosporium spp. and Alternaria spp. On the other hand, in watermelon was detected single and mixed infections of PRSV-W, WMV and ZYMV species, and higher frequency of Fusarium spp. and Alternaria spp.. Were not detected the virus CMV and SqMV. The results show the occurrence of various fungal and viral pathogens in pumpkin and watermelon crops located in the backlands of Paraiba and emphasize the importance of using management strategies that reduce the damage caused by these pathogens.